Contenido radial y su impacto en el desarrollo cultural de los jóvenes de la Parroquia 10 de Noviembre del cantón Ventanas, año 2022 - Muñoz Alarcón, Angie Katherine (2022)
In the present research work we will announce how a radio program influences the cultural development of the young people of the Parroquia 10 de Noviembre, in the analysis of the general problem we have the importance of promoting values such as personal commitment, solidarity, responsibility , providing them with artistic and cultural activities that strengthen their development through radio content. The objectives developed during the investigations show us how young people tell us about educational cultural radio programs, they do not have cultural knowledge, they have problems relating to people from other cultures, that is why we will try to know the advantages and disadvantages of cultural development. This study indicates the proposals that we will give is a timely and quality cultural radio content for adolescents, Its purpose is to promote culture in young people so that they can relate to different cultures, through radio content, we will publicize cultural activities that allow generate bonds of union between members of the same community customs, traditions and rituals knowledge from generation to generation; through art, poetry, music, clothing, theater, literature, working to facilitate access to a quality cultural and educational environment.